Adok dalam Masyarakat Pepadun Berdasarkan Perspektif Teori Struktural Fungsional - Sari, Maya; Karsiwan, Karsiwan (Universitas Tanjungpura, 2025)
This study examines the key issue of the role and function of adok as an honorary title in the Lampung Pepadun community, which is closely linked to piil pesenggiri cultural values, customary norms, and the community’s social structure. The aim of this research is to analyze how adok functions in maintaining social order, strengthening cultural identity, and preserving customary continuity through the lens of structural functionalism theory developed by Talcott Parsons. This study employs a qualitative descriptive method with an ethnographic approach. Data were collected through in-depth interviews with customary leaders and community members, participatory observation during the Begawi Cakak Pepadun ceremony, and documentation of traditional archives and activity photos. The findings reveal that adok has a structural function as a regulator of social stratification, a reinforcer of cultural identity, and a medium for social integration. Within Parsons’ AGIL framework, adok contributes to social adaptation, goal attainment, integration, and the maintenance of cultural patterns. The implications of this study emphasize that adok is not merely a symbolic title but an essential instrument in sustaining social stability and preserving local culture in the face of modernization.